The Effect Of Ovaprim Injections Combination With Oxytocin On Ovulation Stimulation And The Quality Of Egg Hoven’s Carp (Leptobarbus Hoevenii Blkr) - Michael Franciscus Nainggolan; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractResearch on the effect of ovaprim injections combination with oxytocin on ovulation stimulation and the quality of egg hoven’s carp(Leptobarbus Hoevenii Blkr.) was conducted on August - September 2018 at Domestic Harcery BPBAT  Gelam River Jambi, under Directorat General of Aquaculture Ministry of Marine Affairs and Fisheries. The purpose of this study was to determine the effect of combining different doses of ovaprim and oxytocin on the ovulation stimulation and the quality of egg hoven’s carp and to know the best combination of ovaprim dose and oxytocin for ovulation and quality of egg hoven’s carp. The Method used is an experimens method using a complete randomized design with four treatments and three repetitions. The treatments used was P0 (Ovaprim 7 ml/kg body weight), P1 (Ovaprim 0,525 ml/kg + Oxytocin 0,175 Iu/kg body weight), P2 (Ovaprim 0,35 ml/kg + Oxytocin 0,35 Iu/kg body weight), dan P3 (Ovaprim 0,175 ml/kg + Oxytocin 0,525 Iu/kg body weight). The results showed that giving ovaprim 0,35 ml/kg + oxytocin 0,35 Iu/kg body weight gave the best  result with the latent time obtained 12,88 hours,  number of eggs resulted stripping 35 (parent item/gram), value of ovisomaic index 8,4%, increase of egg maturity 9 %, value of fertilization 85,33%. value of hatching 74,91%, survival rate 75,55 % and injection costs of Rp. 12.105 for one spawning cycle.Keywords : Hoven’s Crap, Leptobarbus hoevenii Blkr, ovaprimdose,oxytocin dose,               ovulation and egg quality .